The Arabidopsis Transcription Factor ANAC032 Represses Anthocyanin Biosynthesis in Response to High Sucrose and Oxidative and Abiotic Stresses - Mahmood, Kashif; Xu, Zhenhua; El-Kereamy, Ashraf; Casaretto, José A.; Rothstein, Steven J. (Frontiers in Plant Science, 2016)
Production of anthocyanins is one of the adaptive responses employed by plants during stress conditions. During stress, anthocyanin biosynthesis is mainly regulated at the transcriptional level via a complex interplay between activators and repressors of anthocyanin biosynthesis genes. In this study, we investigated the role of a NAC transcription factor, ANAC032, in the regulation of anthocyanin biosynthesis during stress conditions. ANAC032 expression was found to be induced by exogenous sucrose as well as high light (HL) stress. Using biochemical, molecular and transgenic approaches, we show that ANAC032 represses anthocyanin biosynthesis in response to sucrose treatment, HL and oxidative stress. ANAC032 was found to negatively affect anthocyanin accumulation and the expression of anthocyanin biosynthesis (DFR, ANS/LDOX) and positive regulatory (TT8) genes as demonstrated in overexpression line (35S:ANAC032) compared to wild-type under HL stress. The chimeric repressor line (35S:ANAC032-SRDX) exhibited the opposite expression patterns for these genes. The negative impact of ANAC032 on the expression of DFR, ANS/LDOX and TT8 was found to be correlated with the altered expression of negative regulators of anthocyanin biosynthesis, AtMYBL2 and SPL9. In addition to this, ANAC032 also repressed the MeJA- and ABA-induced anthocyanin biosynthesis. As a result, transgenic lines overexpressing ANAC032 (35S:ANAC032) produced drastically reduced levels of anthocyanin pigment compared to wild-type when challenged with salinity stress. However, transgenic chimeric repressor lines (35S:ANAC032-SRDX) exhibited the opposite phenotype. Our results suggest that ANAC032 functions as a negative regulator of anthocyanin biosynthesis in Arabidopsis thaliana during stress conditions.